2007
DOI: 10.4103/0250-474x.34555
|View full text |Cite
|
Sign up to set email alerts
|

Studies to enhance dissolution properties of carbamazepine

Abstract: Carbamazepine a dibenzapine derivative with structural resembling to the tricyclic antidepressant, it is used to control some types of seizures in the treatment of epilepsy. It is also used to relieve pain due to trigeminal neuralgia. One of the major problems with this drug is its very low solubility in biological fl uids, which results into poor bioavailability after oral administration. Hence present study was carried out to enhance dissolution properties of carbamazepine. Physical mixtures and solid disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…This could be another reason for high dissolution rate of solid disper- sion samples containing low concentration of carrier in comparison with the samples containing high concentration of carrier. Similar results were reported for CBZ solid dispersion samples when the concentration of PVP-K30 was increased from 40 to 160 mg [17]. The figures shows that no further improvement in dissolution of CBZ occurred when the amount of carrier was increased from 33.3% (ratio of drug to carrier 2:1) to 80% (ratio of drug:carrier 1:4) (Fig.…”
Section: Dissolution Studiessupporting
confidence: 90%
“…This could be another reason for high dissolution rate of solid disper- sion samples containing low concentration of carrier in comparison with the samples containing high concentration of carrier. Similar results were reported for CBZ solid dispersion samples when the concentration of PVP-K30 was increased from 40 to 160 mg [17]. The figures shows that no further improvement in dissolution of CBZ occurred when the amount of carrier was increased from 33.3% (ratio of drug to carrier 2:1) to 80% (ratio of drug:carrier 1:4) (Fig.…”
Section: Dissolution Studiessupporting
confidence: 90%
“…It can be observed that the dissolution of pure CLOT in distilled water was very low with less than 14% of the drug was dissolved within 120 min. This is could be ascribed to poor wettability and/or agglomeration or particle size[ 33 ]. Co-habitation of carriers with CLOT in physical mixtures, clearly improved the dissolution rate of the drug and this could be attributed to wettability improvement of CLOT particles[ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…12 Powder X-ray Diffraction Studies Using of XRD patterns were recorded using BRUKER-axs D8-ADVANCE, model generator Powder, X-ray diffraction patterns, were used to determine intensities and position of diffraction peaks were considered for comparison and identification of crystallinity of the drug or carrier. 13,14 Scanning Electron Microscopy Using scanning electron microscopy to determine the external morphology of pure drug and solid dispersion. Solid dispersion was coated with gold-palladium alloy using coat ion sputter.…”
Section: Differential Scanning Calorimetermentioning
confidence: 99%